Calcium signaling facilitates chilling- and GA- induced dormancy release in tree peony - Gai, Weiling; Liu, Chunying; Yang, Mengjie; Li, Feng; Xin, Hua; Gai, Shupeng (Frontiers in Plant Science, 2024)
Calcium plays a crucial role in plant growth and development, yet little is known about its function in endodormancy regulation. Tree peony (Paeonia suffruticosa), characterized by compound buds and large flowers, is well-known for its ornamental and medicinal value. To break bud dormancy release is a prerequisite of flowering and forcing-culture, particularly during Spring Festival. In this study, the Ca 2+ chelator EGTA and Ca 2+ channel blockers LaCl3 were applied, resulting in a significant delay in budburst during both chilling-and gibberellin (GA)-induced dormancy release in a dosage-dependent manner. As expected, the retardation of bud break was recovered by the supplementation of 30 mM CaCl2, indicating a facilitating role of calcium in dormancy release. Accordingly, several calcium-sensor-encoding genes including Calmodulin (CaM) and Ca 2+ -dependent protein kinases (CDPKs) were significantly up-regulated by prolonged chilling and exogenous GAs. Ultrastructure observations revealed a decline in starch grains and the reopening of transport corridors following prolonged chilling. Calcium deposits were abundance in the cell walls, intercellular spaces at the early dormant stage, but enriched in the cytosol and nucleus before dormancy release. Additionally, several genes associated with dormancy release, including EBB1, EBB3, SVP, GA20ox, RGL1, BG6, and BG9, were differentially expressed after calcium blocking and recovery treatments, indicating that calcium might partially modulate dormancy release through GA and ABA pathways. Our findings provide novel insights into the mechanism of dormancy release and offer potential benefits for improving and perfecting forcing culture technology in tree peonies.